Hostility, Harassment, and Violence: On the Limits of ‘Free Speech’ for Minority Feminist Scholars - Bourgeois, Robyn (Atlantis)

(untitled) (Mount Saint Vincent University, 2020)
Following the rich tradition of Indigenous and Black feminists and authors, this article makes use of storytelling to explore the limits of freedom of speech in the academy for feminist scholars belonging to socially marginalized groups and, particularly, Indigenous feminist scholars. Through autoethnography, I expose the ways that freedom of speech was been weaponized against me by people with power to silence and suppress my freedom of speech. Moreover, I draw attention to the ways this has been done to me in order to secure the freedom of speech of other dominant and powerful people. This paper concludes with some recommendations about disrupting this violence and better supporting feminist scholars from minority groups.